Structural grading of three sympodial bamboo culms (Hitam, Andong, and Tali) subjected to axial compressive load. (15th February 2019) - Bahtiar, Effendi Tri; Imanullah, Alif Puguh; Hermawan, Dede; Nugroho, Naresworo; Abdurachman,
Highlight: Structural grading of bamboo culm could be conducted by using strength or capacity grading. Density is good predictor for estimating the compressive strength, while linear mass is the best one for estimating the load carrying capacity. Capacity approached is better than strength approach in bamboo construction design. Abstract: Bamboo culm is commonly utilized in columns that are subjected to axial compressive load, thus it is necessary to measure its compressive strength and load-carrying capacity. The variability of culm dimension, geometry, moisture content, density, and linear mass of three sympodial bamboo species belonging to the Gigantochloa genus [Hitam ( Gigantochloa atroviolacea ), Tali ( G. apus ), and Andong ( G. pseudoarundinacea )] were studied to determine the best predictor for structural grading of these culms based on their compression properties. Two types of structural gradings, strength and capacity gradings, were examined. Strength grading was developed assuming a hollow or solid circular section of the bamboo culm. Both strength and capacity gradings sufficiently classified culms of all three species into several structural quality classes based on a strong correlation ( r ) between the predictor and dependent variable ( r  = 0.83–0.97); however, capacity grading proved to be the best type of structural grading because the maximum compressive load carrying capacity ( Fc ) of bamboo culm could be predicted more precisely and accurately compared with the compressive strength ( σc ). Additionally, it was found that linear mass was the best predictor for estimating the compressive capacity ( Fc ) ( r  = 0.89–0.98), culm density for estimating compressive strength assuming a solid circular section ( σcc ) ( r  = 0.84–0.92), and wall density for estimating compressive strength assuming a hollow circular section ( σcw ) ( r  = 0.73–0.89). Based on these predictors, capacity and strength gradings for bamboo culms subjected to compressive load were developed, permitting categorization of bamboo culms into structural quality classes. Each structural quality class had a 5% lower value and characteristic value for σc and the maximum compressive load, which became design values for bamboo structural design.